Magnetic Susceptibility Profile, Fe Content and pH Analysis of Apple Orchard Soil and the Relation to Fruit Diameter - Siti Zulaikah; Yoyok Adisetyo Laksono; Dewi Ningsih; Ninik Munfarikha; Rizka Amirul Hikma (Jurnal Penelitian Pendidikan IPA, 2022)
The measurement of magnetic susceptibility, pH, element concentration of Fe and apples diameter has been conducted in orchard soil of Malang, East Java Indonesia. The measurement was performed in two orchards, namely Pujon and Poncokusumo with two different kind of apples in each orchard. This research aimed at exploring in detail linked between magnetic properties, the existence of magnetic mineral as magnetic property carrier in the soil, soil pH, as well as the size of apple diameter to evaluate the quality of apple production in the both areas. The results shows that the soil with lower susceptibility, it was expected that the magnetic mineral of magnetic property carrier to be smaller, low soil pH, meaning that the soil was more acidic which implied on a larger size of apple diameter for Rumbeauty type of apple. Meanwhile, when the soil had a higher susceptibility, and it is expected that the magnetic mineral is also high as well as having high pH, this growing media is appropriate to develop Manalagi type of apple. Based on the observed soil magnetic properties and pH from both observed orchards, it can be suggested that Manalagi apple is appropriate to be planted in Poncokusumo area, while Rumbeauty is appropriate to grow in Pujon area.